2010
DOI: 10.1136/jnnp.2009.203323
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of intracranial vertebral artery asymmetry to vestibular neuropathy

Abstract: VAH may serve as a regional haemodynamic negative contributor and impede blood supply to the ipsilateral vestibular labyrinth, contributing to the development of VN, which could be enhanced by atherosclerotic risk factors and the left-sided location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Hypoplasia of V 4 remains an uncommon embryogenic variation of the posterior circulation, which could have important haemodynamic implications (hypoperfusion and insufficient circulation) in acute brainstem/cerebellar ischaemic stroke [17,19], or in the lateralisation of vestibular neuropathy [8]. In the pathoanatomical studies, hypoplastic VA is defined as a lumen diameter of < 3, < 2.5, < 2.2 or < 2 mm, and there is no consensus on this value [7,19].…”
Section: Hypoplasia Of the Vertebral Arterymentioning
confidence: 99%
“…Hypoplasia of V 4 remains an uncommon embryogenic variation of the posterior circulation, which could have important haemodynamic implications (hypoperfusion and insufficient circulation) in acute brainstem/cerebellar ischaemic stroke [17,19], or in the lateralisation of vestibular neuropathy [8]. In the pathoanatomical studies, hypoplastic VA is defined as a lumen diameter of < 3, < 2.5, < 2.2 or < 2 mm, and there is no consensus on this value [7,19].…”
Section: Hypoplasia Of the Vertebral Arterymentioning
confidence: 99%
“…Furthermore, VAH served as an independent factor for a reduction of posterior circulation blood flow velocity and may contribute to vertebro‐basilar ischemic events particularly in the territory of the posterior inferior cerebellar artery (PICA) since it limits the potential of compensatory flow in case of major intracranial occlusion . In general, VAH has been related to several diseases: symptomatic or asymptomatic pontine infarctions were reported to be more common, basilar artery occlusions were found to be more frequent in VAH than in cases with nonbrainstem infarctions, and migraine with aura and vestibular neuronitis . The episodic dizziness with sensori‐neural hearing impairment associated with recurrent hemodynamic decrease of the Intracranial Vertebral‐Basilar Artery Hypoplasia was also associated with VAH …”
Section: Introductionmentioning
confidence: 97%
“…1 In general, VAH has been related to several diseases: 1 symptomatic or asymptomatic pontine infarctions were reported to be more common, 7 basilar artery occlusions were found to be more frequent in VAH than in cases with nonbrainstem infarctions, 8 and migraine with aura and vestibular neuronitis. 9,10 The episodic dizziness with sensori-neural hearing impairment associated with recurrent hemodynamic decrease of the Intracranial Vertebral-Basilar Artery Hypoplasia was also associated with VAH. 11 Since VAH is not a rare finding and it might be clinically relevant, we were interested to investigate whether the variation in VA diameter and flow is genetically influenced.…”
Section: Introductionmentioning
confidence: 99%
“…3 No standard definition of this condition according to vessel diameter has been established, 3,4 but operational definitions have been based on diameters of ,2 to ,3 mm or caliber discrepancy $1:1.7. 8,9 Moreover, emerging evidence from case reports has suggested that VAH is a predisposing factor for spontaneous VA dissection (sVAD). 4 VAH has been insufficiently studied, but in the past years, VAH has been given increasing attention because of accumulating evidence suggesting it is not a benign vessel variant, as previously believed.…”
mentioning
confidence: 99%